2013
DOI: 10.3409/fb61_1-2.11
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Poly(L-lactide) versus Poly(L-Lactide-co-Trimethylene Carbonate) on Biological Characteristics of Fibroblasts and Osteoblasts*

Abstract: Bone tissue loss due to injury or disease often requires application ofautologous tissue grafts or artificial biomaterials to fill the fracture. Synthetic biomaterials provide temporary structural support for bone tissue and can be subsequently colonized by host tissue-specific cells. One of the most investigated groups of biomaterials are degradable polymers that naturally decompose in tissues with time. In particular aliphatic polyesters such as polylactides were reported to fulfill biocompatibility requirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Furthermore, an increased lactate level followed by polymer breakdown can decrease the amount of intracellular radical oxygen species, reducing the intracellular redox state [ 6 ]. Though biocompatible, with its long degradation period, chronic inflammation is still observed with PLLA with the appearance of pro-inflammation cytokines (IL-1β, TNF and MCP-1) [ 118 , 119 ], even though the metabolism study of this chronic inflammation is still lacking.…”
Section: Metabolomics For Development Of Bone Disease Treatment Methodsmentioning
confidence: 99%
“…Furthermore, an increased lactate level followed by polymer breakdown can decrease the amount of intracellular radical oxygen species, reducing the intracellular redox state [ 6 ]. Though biocompatible, with its long degradation period, chronic inflammation is still observed with PLLA with the appearance of pro-inflammation cytokines (IL-1β, TNF and MCP-1) [ 118 , 119 ], even though the metabolism study of this chronic inflammation is still lacking.…”
Section: Metabolomics For Development Of Bone Disease Treatment Methodsmentioning
confidence: 99%
“…However, when compared to TCPS, the proliferation ratio of fibroblasts cultured on these scaffolds was significantly decreased [36]. Studies performed previously by our group showed that PLGA processed into form foils stimulated the typical functions of L929 fibroblasts [26,27,37] and did not induce the release of proinflammatory cytokines from macrophages [29]. Moreover, PLGA foils were found to degrade almost completely after 30 weeks of implantation into rat skeletal muscle [32].…”
Section: Discussionmentioning
confidence: 89%
“…In previous studies, we performed in vitro and in vivo analyses of several resorbable aliphatic polyesters containing L-lactide, glycolide, ε-caprolactone and trimethylene carbonate with the aim of using them in bone tissue engineering [24][25][26][27]. All of our materials were synthesized with the use of a biocompatible initiator (zirconium (IV) acetylacetonate), in contrast to typically applied tin compounds [28,29].…”
Section: Introductionmentioning
confidence: 99%